Uwarunkowania zdrowia psychicznego nauczycieli w kontekście stresu zawodowego = Determinants of teachers' mental health in the context of occupational stress - Olejniczak, Dominik; Gebel, Adelina; Religioni, Urszula; Skonieczna, Joanna; Zakrzewska, Karolina (Journal of Education, Health and Sport, 2015)
Olejniczak Dominik, Gebel Adelina, Religioni Urszula, Skonieczna Joanna, Zakrzewska Karolina. Uwarunkowania zdrowia psychicznego nauczycieli w kontekście stresu zawodowego = Determinants of teachers' mental health in the context of occupational stress. Journal of Education, Health and Sport. 2015;5(11):159-169. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33692 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A159-169 https://pbn.nauka.gov.pl/works/668507 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. Uwarunkowania zdrowia psychicznego nauczycieli w kontekście stresu zawodowego Determinants of teachers' mental health in the context of occupational stress Dominik Olejniczak1 Adelina Gebel2 Urszula Religioni3 Joanna Skonieczna1 Karolina Zakrzewska4,5 1 Warszawski Uniwersytet Medyczny, Zakład Zdrowia Publicznego, ul. Banacha 1a, 02-097 Warszawa 2 Studenckie Koło Naukowe Zdrowia Publicznego, ul. Banacha 1a, 02-097 Warszawa 3 Szkoła Główna Handlowa, Kolegium Ekonomiczno-Społeczne, ul. Wiśniowa 41, pok. 53 02-520 Warszawa 4 Warszawski Uniwersytet Medyczny, Zakład Epidemiologii, ul. Oczki 3, 02-007 Warszawa 5 Narodowy Instytut Zdrowia Publicznego-Państwowy Zakład Higieny, Zakład Wirusologii, ul. Chocimska 24, 00-791 Warszawa Słowa kluczowe: uwarunkowania zdrowia, nauczyciel, stres. Key words: health determinants, teacher, occupational stress. Streszczenie Wykonywanie zawodu nauczyciela niesie ze sobą wiele satysfakcji, ale wiąże się również z narażeniem na wiele zagrożeń zdrowia, specyficznych dla tego zawodu. Identyfikacja zagrożeń pozwoli na zmniejszenie ryzyka wystąpienia ich i poprawi tym samym stan zdrowia tej grupy zawodowej. Celem niniejszej pracy jest określenie uwarunkowań stresu wśród nauczycieli, jego objawów, sposobów radzenia sobie z nim, a także poszukiwanie związków stresu z płcią, wiekiem, stażem i miejscem pracy. W badaniu wzięło udział 440 nauczycieli pracujących w szkołach podstawowych, gimnazjalnych, ponadgimnazjalnych oraz szkołach muzycznych. Na podstawie uzyskanych wyników wywnioskowano, iż istnieje konieczność intensyfikacji działań profilaktycznych w grupie nauczycieli, którzy w swojej pracy doświadczają czynników przyczyniających się do występowania stresu zawodowego. Działania powinny być skierowane zarówno na redukcję (lub pomniejszenie oddziaływania) samego czynnika oraz na rozwijanie umiejętności radzenia sobie ze stresem nim spowodowanym. Abstract Teaching profession carries with it a lot of satisfaction, but also is associated with exposure to many health hazards specific to the profession. Their identification will help to reduce the risk of threats, thereby improve the health of this professional group. The aim of this study is to determine the conditions of stress among teachers, its symptoms, how to deal with it, as well as seeking relationships stress to gender, age, seniority and place of work. The study involved 440 teachers working in schools, primary schools, middle schools, secondary schools and music schools. Based on these results it was concluded that The existence need to intensify prevention in a group of teachers who in their work experience factors that contribute to the incidence of occupational stress. Actions should be directed both to reduce (or reduce the impact) same factor and to develop skills to cope with stress it caused.